Exploring Jalaluddin Rumi’s Hermeneutic of Love, Patience and Destiny in Relation to the Meaning of Life - Taufiqurrahman, Taufiqurrahman; Putri, Endrika Widdia; Pratama, Dimas Rozi (Journal of Al-Tamaddun, 2024)
Jalaluddin Rumi (1207 – 1273 CE) was a prominent Muslim poet of the Middle Ages, renowned for his profound poetry, which reflects a synthesis of Sufi philosophy and aesthetic language. The enduring significance of his work, alongside its inherent values, has consistently invited critical analysis. This article seeks to examine Rumi’s poetry, specifically focusing on the themes of love, patience, and destiny, through a hermeneutical lens. The findings indicate that the poetry of Jalaluddin Rumi articulates the connection between humanity and the Divine, particularly through the exploration of these three interconnected themes. It can be posited that the acceptance of one's fate or destiny signifies an expression of love toward God, even when such a fate may be perceived as unfavorable. Consequently, patience emerges as a necessary course of action, as it is understood that underlying any given destiny is God’s invisible love, which becomes apparent over time. The development of meaning pertaining to life within this context suggests that individuals should endeavor to comprehend their existence in this world as part of a divine narrative orchestrated by God, who has meticulously arranged it to be optimal and perfect.